PENGARUH LAYANAN INFORMASI TENTANG WAWASAN KARIR TERHADAP ASPIRASI KARIR SISWA KELAS X BB DAN DKV SMK NEGERI 4PEKANBARU T.P 2014/2015 - M.Syafaruddin '; Zulfan Saam Saam; Abu Asyari Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Aspiration is the hope for the success of a person in realizing the desired career destination. But at the moment many students who could not think of a direction in planning your career. Hopes of success in achisving career is not yet offset by the knowledge the students for career insights, leaving students wrong in choosing majors. This research aims. 1) to know the description of the career aspirations of students prior knowledge given the information services about career insights. 2) to know the process of granting information services about career aspirations for career insights. 3) to know the description of the career aspirations of students after the knowledge given the information services about career insights. 4) to find out the level of knowledge of students ' career aspirations before with service after being given information about the career insights. 5) to know how big is the influence of information services about career aspirations for career insight students. Data collection tools in the form of scale career aspirations. The subject of research is the grade X BB and DKV SMKN 4 Pekanbaru that add up to 110 people. Determination of a sample using simple saturated. The sample in this study as many as 110 people. The description of the career aspirations of students before the given information services about career insights are in a high category of 54,45%, medium category of 38,18% very high category of 5.45%, and low of 1,82%,. The description of the career aspirations of students after being given information about the career insights are in a higher category of 50%, very high category of 46,37% and medium category of 3.63-%. Based on the hypothesis test results are then compared with big tcount and big ttable that is the result of the calculation with the "t" test, 5% error level = 1,968 then it can be seen that tcount is greater than ttable (10 > 1,968) on levels 5% error so it can be concluded that the hypothesis be accepted is there is a significant difference between the career aspirations of students before and after do information services about career insights. Key words: Information Services, Career Aspirations